ANALISIS ARUS KAS OPERASI, LIKUIDITAS DAN LEVERAGE TERHADAP PROFITABILITAS PADA SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dina Wijaya; Noviarti (Jurnal Satya Mandiri Manajemen dan Bisnis, 2022)
This study aims to determine an effect of Operating Cash Flow, Liquidity and Leverage on Profitability in the Food and Beverage Company Sector which are listed on the Indonesia Stock Exchange (IDX). The population in this study is data from food and beverage sector companies listed on the Indonesia Stock Exchange. The sampling technique used is purposive sampling, namely companies that only produce food and soft drinks that are listed on the Indonesia Stock Exchange and have published their financial reports consecutively in 2016-2020. Data analysis techniques used in this study are quantitative and descriptive analysis techniques, classifying positive and negative earnings, classic assumption test, panel data regression analysis, chow test, haussman test, Langrange multiplier test, regression model assumption test and hypothesis testing. The results of the study partially show that Operating Cash Flow has no effect on Profitability, Liquidity has no effect on Profitability, and Leverage has no effect on Profitability. Meanwhile simultaneously operating cash flow, liquidity and leverage affect profitability.